Implementation of the E-Visum Application on the Discipline of Family Planning Extension Employees in Dp2kbp3a, Subang Regency - Nabila Santosa; Mochamad Raka Abizar; Nuraisyah; Ameyda Noor Maulydyani; Shinta Octaviana (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2025)
Abstract Digital transformation in bureaucracy is an essential step toward achieving efficient and accountable public governance. One form of this initiative is the implementation of the e-Visum application at the Office of Population Control, Family Planning, Women Empowerment, and Child Protection (DP2KBP3A) of Subang Regency, which serves as a digital tool for monitoring attendance and performance of family planning field officers. This study aims to analyze how the e-Visum system influences employee discipline and to identify the supporting and inhibiting factors in its implementation. This research employs a qualitative approach with a case study method, collecting data through in-depth interviews, field observations, and document analysis. Data were analyzed interactively using the Miles and Huberman model, including data reduction, data display, and conclusion drawing. The findings reveal that the e-Visum application positively impacts employee discipline by improving punctuality, reporting accountability, and work responsibility. Nevertheless, technical challenges such as limited internet access and varying digital literacy levels remain obstacles. The study recommends enhancing human resource capacity and strengthening technological infrastructure to ensure the system’s effective and sustainable implementation. Keywords: Bureaucratic Digitalization, E-Visum, Employee Discipline, Local Government, Policy Implementation.